Difficulty of Learning English Language by Turkish Nationalities and Learning Turkish Language by Foreign Students in Turkey: A Case Study for Elazig Metropolis - Muhammad, Jamila; Varol, Asaf (Fırat University, 2019)
Learning any language as a second language is generally considered difficult due to some contributing factors.  English language being the top global language, has made it a necessity for Turkish natives to learn the language at all levels of Education. Foreign students in Turkey on the other hand, has to learn the Turkish language and present a proficiency certificate before they are being absorbed into their respective course of study departments. This study hypothesized that, the factors determining difficulty in learning English by Turkish natives are the same factors causing difficulty in learning Turkish language by foreign students in Turkey. Paired sample t-test was used as a statistical measure to investigate the statistical significance between variables of interest that aid the difficulty in learning these two languages.